Improving the therapeutic profile of MSCs: Cytokine priming reduces donor-dependent heterogeneity and enhances their immunomodulatory capacity - Jaris Valencia; Jaris Valencia; Jaris Valencia; Rosa M. Yáñez; Rosa M. Yáñez; Rosa M. Yáñez; Sandra Muntión; Sandra Muntión; Sandra Muntión; María Fernández-García; María Fernández-García; María Fernández-García; et al. (Frontiers in Immunology)
IntroductionMSCs exhibit regenerative, anti-inflammatory and immunomodulatory properties due to the large amount of cytokines, chemokines and growth factors they secrete. MSCs have been extensively evaluated in clinical trials, however, in some cases their therapeutic effects are variable. Therefore, strategies to improve their therapeutic potential, such as preconditioning with proinflammatory factors, have been proposed. Several priming approaches have provided non-conclusive results, and the duration of priming effects on MSC properties or their response to a second inflammatory stimulus have not been fully addressed.MethodsWe have investigated the impact of triple cytokine priming in MSCs on their characterization and viability, their transcriptomic profile, the functionality of innate and acquired immune cells, as well as the maintenance of the response to priming over time, their subsequent responsiveness to a second inflammatory stimulus.ResultsPriming MSCs with proinflammatory cytokines (CK-MSCs) do not modify the differentiation capacity of MSCs, nor their immunophenotype and viability. Moreover, cytokine priming enhances the anti-inflammatory and immunomodulatory properties of MSCs against NK and dendritic cells, while maintaining the same T cell immunomodulatory capacity as unstimulated MSCs. Thus, they decrease T-lymphocytes and NK cell proliferation, inhibit the differentiation and allostimulatory capacity of dendritic cells and promote the differentiation of monocytes with an immunosuppressive profile. In addition, we have shown for the first time that proinflammatory priming reduces the variability between different donors and MSC origins. Finally, the effect on CK-MSC is maintained over time and even after a secondary inflammatory stimulus.ConclusionsCytokine-priming improves the therapeutic potential of MSCs and reduces inter-donor variability.